On the F-pure threshold of the homogeneous maximal ideal of a Stanley-Reisner ring - Badilla-Céspedes, Wágner (2024)
In prime characteristic, the F-pure threshold is a numerical invariant measuring singularities. Few estimates of this number are known. In this note, we explicitly compute the F-pure threshold of the homogeneous maximal ideal in a Stanley-Reisner ring and prove that this number and the splitting dimension are same.